Correction: COMPARE CPM-RMI Trial: Intramyocardial Transplantation of Autologous Bone Marrow-Derived CD133+ Cells and MNCs during CABG in Patients with Recent MI: A Phase II/III, Multicenter, Placebo-Controlled, Randomized, Double-Blind Clinical Trial - Mohammad Hassan Naseri (Cell Journal, 2018)
This article published in Cell J (Yakhteh), Vol 20, No 2, Jul-Sep 2018, on pages 267-277, four affiliations (1, 4, 5, and 10) were changed based on authors request.